Interactive Learning Initiatives Utilizing Fossil Discoveries at Tambaksari Junior High School, Indonesia - Isana, Widiati; Lestari, Fathia; Dold, Katja (International Journal of Social Learning (IJSL), 2025)
This study aims to show that interactive learning techniques can increase historical awareness amongst students. Using the interactive learning experience of searching for and categorising fossils in the local river bed by SMPN Tambaksari (hereafter referred to as Tambaksari Junior High School) students between 1980 and 1996. The historical method to select and evaluate both oral and written sources. The oral sources include interviews with the participants of the fossil digs. Written sources included news and magazine articles published during the time of the digs. The results show that the interactive teaching method was considered a meaningful and positive learning experience by students. Additionally, it was found that the students expanded their historical awareness by gaining an appreciation for the connection of history with the present and the future. Finally, there was a positive personal development for students, who learned about themselves and their relationship with their culture and nation.